Removal of azo dye from aqueous solution by a low-cost activated carbon prepared from coal: adsorption kinetics, isotherms study, and DFT simulation - Jan, Saeed Ullah; Ahmad, Aziz; Khan, Adnan Ali; Melhi, Saad; Ahmad, Iftikhar; Sun, Guohua; Chen, Cheng-Meng; Ahmad, Rashid (Environmental science and pollution research international, 2021)
The high-risk organic pollutants produced by industries are of growing concern. The highly porous coal-based activated carbon (AC) having a specific surface area of 3452.8 m 2 /g is used for the adsorption of azo dye from synthetic solution. The sorbent is characterized through BET, SEM, TEM, XRD, FT-IR, TGA, and zeta potential. The sorbent exhibits − 18.7 mV surface charge, which is high enough for making suspension. The maximum dye uptake of 333 mg/g is observed in sorbent under acidic medium. The thermodynamics parameters like ∆G , ∆H , and ΔS were found to be − 12.40 kJ mol −1 , 39.66 kJ mol −1 , and 174.55 J mol −1 K −1 at 293 K, respectively, revealing that the adsorption mechanism is spontaneous, endothermic, and feasible. The experimental data follows the Langmuir and D–R models. The adsorption follows pseudo 2nd-order kinetics. DFT investigation shows that the dye sorption onto AC in configuration No. 4 (CFG-4) is more effective, as this configuration has high ∆H (enthalpy change) and adsorption energy (E ads ). This is confirmed by Mullikan atomic charge transfer phenomenon.